The Effectiveness of Using the Polya Strategy in Understanding the Concepts of Teaching Methods among Students of the College of Education - Saman Ahmed Abdulla; Tarq Hashm Khamis (Zanco Journal of Human Sciences, 2026)
This study was sought to examine the efficacy of the Polya strategy in enhancing conceptual comprehension within the Teaching Methods course among third-year students enrolled in the College of Education. To achieve this objective, a cognitive test was administered to both experimental and control groups. The findings revealed a significant advantage in favor of the experimental group, indicating that the Polya strategy substantially outperforms traditional instructional methods in fostering deeper conceptual understanding. These results underscore the strategic value of structured problem-solving approaches in promoting meaningful learning outcomes across pedagogical contexts. Moreover, the Polya strategy was found to play a pivotal role in cultivating higher- order thinking skills-including analysis, synthesis, and evaluation—alongside critical and creative thinking competencies. As learners engage with complex problems, they are required to deconstruct them into fundamental components, discern interrelationships, evaluate potential solutions, and select the most effective course of action. Such cognitive engagement fosters not only a profound grasp of abstract concepts but also the capacity to apply them flexibly in diverse educational scenarios.